The Relationship Between Soil Physics Characteristics with Nilam Production at Pasie Raja Sub-District South Aceh Regency - Harwika; Dina Miftahul Jannah; Ihsan; Irwansyah; Balkhaya (Jurnal Inotera, 2026)
Patchouli (Pogostemon cablin) cultivated in Pasie Raja District, South Aceh Regency, is widely recognized for its high-quality essential oil and distinctive aroma. However, despite favourable climatic conditions, patchouli production in this region declined substantially in 2023, reaching only 130 tons, which is considerably lower than the national average. This decline is presumed to be partly associated with soil fertility constraints, particularly soil physical properties. This study aimed to analyse the relationship between selected soil physical characteristics and patchouli productivity in Pasie Raja District. The research was conducted at six patchouli cultivation sites, with soil physical analyses performed at the Materials Testing Laboratory of Politeknik Aceh Selatan. Statistical analysis was carried out using Microsoft Excel to examine the relationships between soil porosity, bulk density, effective soil depth, and patchouli yield. The results indicated that bulk density showed a positive correlation with patchouli productivity, explaining 23.23% of yield variation. Soil porosity also exhibited a positive correlation, accounting for 16.68% of yield variation, while effective soil depth had the strongest association, explaining 36.3% of the variation in patchouli yield. These findings suggest that soil physical characteristics play an important role in patchouli production and may serve as a scientific basis for improving soil management practices to enhance patchouli productivity.